Deforestation in the Brazilian Amazon from the perspective of cattle ranching: the degradation of water resources in the context of the northern region of Mato Grosso (Research, Society and Development, 2021)
The study aimed to establish a relationship between the deforestation process, the expansion of cattle ranching in the Brazilian Amazon and the degradation of water bodies. The investigation followed a qualitative approach, with bibliographic review procedures and data survey on deforestation and cattle ranching in the states of the Legal Amazon, as a way of contextualizing the chain of developmental projects since the 1970s. Focusing on an area located in the Amazon biome, in the north of Mato Grosso, information was collected from municipalities in the macro-region, named by the Mato Grosso Institute of Agricultural Economics, as North 2. Based on data from PRODES and IBGE-SIDRA, in the period between 1985 and 2020, it was observed that most of the deforested areas were occupied by cattle ranching, being, therefore, the largest vector of deforestation. The suppression of the forest and the inadequate management of the soil directly compromise water resources. In addition, without respecting the environmental legislation for the preservation of Permanent Protection Areas (APPs), the activity caused intense environmental degradation, greatly affecting the riparian forests by felling and burning, which implied in the vitality (quantity and quality of water) of the springs, streams and rivers and loss of ecological function.